Visual workout - Landa, Robin (OnWord Press, 2001)
This one-of-a-kind workbook for graphic designers, which may be used independently or in conjunction with Graphic Design Solutions, 3E by Robin Landa, will stimulate your imagination and enable you to flex your creative design muscles. The exercises in this workbook expand upon graphic design applications and each exercise presents a creative problem intended to stimulate visual thinking, encourage sketching and ideas, and, most importantly, prompt you to try new approaches